Shi nei she ji zhun ze - Arai, Shima; He, Ningyi (Shijiazhuang : Hebei Science and Technology Press, 2022)
The book consists of 4 chapters, including: what is a simple and stylish room; 20 guidelines to create a simple and stylish room; Guidelines for making different spaces more simple and stylish; Zero failed shopping tips.
Keywords: Interior decoration